O sistema comissional e a atuação de interesses organizados: acesso e influência na câmara dos deputados - Ciro Antonio da Silva Resende (2018)
In Brazil, the permanent committees of the House of Representatives are pointed out as relevant arenas to lobbying activities. In these arenas, public hearings are a central space for the defense of demands of pressure groups, through which there is the opportunity to present information to decision makers, establish contacts with other groups and demarcate preferences. Although public hearings are a mechanism for increasing access to committees, this is not equally distributed among organized interests. It is therefore crucial to ask: which actors were present in the permanent committees of the House of Representatives, in the 53rd and 54th legislatures? How accessible are these arenas? The perspective that it works assumes that, acting in the same political environment, groups establish relations among themselves, from which emerges a wide network. Attention is directed for this network, as well as for the policy networks that form in each arena of the commission system, identifying its most central actors. It is argued that these actors have greater opportunities to have resources and information, unlike those that have access restrictions. A great deal of data mobilized in this work come from the research Money and politics: the influence of economic power in the National Congress, developed by Ipea. Among the results, it was observed that there was a significant variation in the number of public hearings and participation in these events among permanent committees, indicating the existence of different dynamics among these arenas. With regard to the actors present at public hearings, the results corroborate with the thesis of a hybrid system of representation, and there is also a strong scrutiny of government sectors, which are relevant actors in the dispute for influence in the decision-making process. It was observed a general scenario characterized by concentration on participation and inequality in access to permanent committees. Based on the social network analysis approach, it verifies that emerges relational indicators significantly different between the commissions, especially about two arenas: the Committee of Economic Development, Industry, Commerce and Services and the Committee of Working, Administration and Public Service. The comparison between those jurisdictions reveals differences, which leads to hypotheses about this aspect and points the way to a future research agenda.